2016
DOI: 10.1111/jcmm.12915
|View full text |Cite
|
Sign up to set email alerts
|

Naoxintong attenuates Ischaemia/reperfusion Injury through inhibiting NLRP3 inflammasome activation

Abstract: Naoxintong (NXT) is a Chinese Materia Medica standardized product extracted from 16 various kinds of Chinese traditional herbal medicines including Salvia miltiorrhiza, Angelica sinensis, Astragali Radix. Naoxintong is clinically effective in treating ischaemia heart disease. Nucleotide‐binding oligomerization domain‐Like Receptor with a Pyrin domain 3 (NLRP3) inflammasome has been critically involved in myocardial ischaemia/reperfusion (I/R) injury. Here, we have been suggested that NXT might attenuate myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…The expressions of NLRP3, caspase-1, and SIRT1 in heart tissue and H9c2 cells at the protein level were determined by Western blotting analysis as previously described (Wang et al, 2017). Briefly, cardiac tissues and cells were minced and lysed in ice-cold radioimmunoprecipitation assay (RIPA) lysis buffer.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…The expressions of NLRP3, caspase-1, and SIRT1 in heart tissue and H9c2 cells at the protein level were determined by Western blotting analysis as previously described (Wang et al, 2017). Briefly, cardiac tissues and cells were minced and lysed in ice-cold radioimmunoprecipitation assay (RIPA) lysis buffer.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…The NLRP3 inflammasome has previously been proposed as a potential therapeutic target to treat multiple inflammatory diseases [162][163][164][165][166][167][168][169]. Several synthetic [162][163][164][165]167] and natural [166,168] compounds with varying specificity for the NLRP3 pathway have been tested. One promising treatment is MCC950, a specific smallmolecule inhibitor of the NLRP3 inflammasome [95].…”
Section: Principle Findingsmentioning
confidence: 99%
“…Naoxintong Capsule (NXT) is derived from a classic traditional Chinese prescription named Bu Yang Huan Wu decoction, which is widely used to treat patients with stroke in China. In recent years, more and more clinical studies indicated that NXT can not only ameliorate brain function and promote the recovery of consciousness, but also reduce the plaque area and carotid intima-media thickness [ 9 , 10 ]. However, there is no comprehensive and systematic evidence to confirm its clinical efficacy in patients with CI and carotid atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%